Vliv sericinových proteinů a jejich derivátů na hmyzí a savčí buňky - Suchanová, Eva (Jihočeská univerzita, 2011)
Effect of commercial sericin extract on cell proliferation was examined in the following cell cultures: HeLa, L929, Vero, HaCaT, WS1, human dermal fibroblasts and primary keratinocytes. Sericin was present in the culture media in concentrations 0.001; 0.005; 0.01; 0.05 and 0.1 per cent, respectively. The rate of cell proliferation was assessed by means of a ?cratch test?. Sericin was also added to the medium used to freeze the cells for storage.
Effect of sericin proteins and their derivates on the insect and mammalian cells